Keunggulan Komparatif dan Kompetitif Sektor Industri Pengolahan di Provinsi Jambi - Wibisono, Eristian; Amir, Amri; Zulfanetti, Zulfanetti (Center for Regional Systems Analysis, Planning and Development (CrestPent) IPB, 2019)
Identification of leading sectors or subsectors is one of the main tasks of the regional government and is an important part of regional development planning before formulating, drafting and establishing a better development policy strategy. The main objective of this research is to analyze and identify subsectors in the manufacturing industry sector that have comparativeness and competitiveness in Jambi Province. Main data of this study are secondary data of districts and cities in Jambi Province during the period 2011?2015 which were sourced from the Central Bureau of Statistics, and Indonesian Ministry of National Development Planning (Bappenas). Data were analyzed using descriptive and quantitative analysis methods, namely Location Quotient analysis and Shift Share analysis. Results of the study show that the manufacturing industry subsector of Jambi Province which can be classified as comparative and competitive subsector are timber/wood products industry, paper/goods industry, rubber/rubber goods industry, and furniture industry